The Effect of Promotion, Web Quality and Ease of Electronic Payment (E-Wallet) Moderated by Positive Emotions on Skincare Impulse Buying - Emanuella, Jessica; Pardede, Ratlan (Green Publisher Indonesia, 2023)
This research aims to examine the effect of promotion, web quality, and ease of electronic payments (E-Wallets) moderated by positive emotions on impulse skin care purchases. Impulse buying is often associated with making relatively faster and instant decisions without requiring a long time to think. Differences in Individual personality can give rise to various experiences when making purchases. Lack of control from consumers signifies their inability to delay gratification, thus leading to impulse buying. This study is quantitative research focusing on a survey through distribution questions. This study employs the PLS 4.0 program to examine the data. The population of this study is People at the productive age of work, 18-55 years. This research shows that Promotions and E-Wallets have a positive and significant effect on Impulsive Buying, and Web Quality does not have a positive and significant effect on Impulsive Buying. Positive Emotions have a positive and significant effect in mediating Promotions and E-Wallets with Impulsive Buying. Positive Emotions do not have a positive and significant effect in moderating Web Quality with Impulsive Buying.